Pengaruh Jumlah UMKM dan Pertumbuhan Tenaga Kerja Terhadap Penerimaan Pajak - Norman Duma Sitinjak (Jurnal Manajemen dan Kewirausahaan, 2018)
This study examines the effect of the number of MSMEs and the growth of labor to tax revenue. This research finds that the number of MSMEs has a significant effect on tax revenue. The higher the number of MSMEs, the higher the tax revenue. The growth of labor has no effect on tax revenue.https://doi.org/10.26905/jmdk.v6i1.2065